Quality Assessment of Rain Water Around a Cement Factory in Benue State, Nigeria - Ipav, Selumun Solomon; Dasofunjo, Kayode; Asaar, Godwin Bem (Richtmann Publishing, 2012)
This study was aimed at determining the physico-chemical properties of rainwater collected from a cementfactory and its environment. Four (4) locations labeled A, B, C and D were sampled and analysed. Theresult of the rainwater analysed indicated that locations A, B, C and D had temperature values of 22.3,21.7, 23.5, and 21.8oC respectively, Turbidity; (0.15, 0.18, 0.20 and 0.13 NTU), pH: (6.5, 6.4, 6.1, and 6.7),Hardness as CaCO3: (40.00, 40.00, 40.00 and 40.33 mg/L), NO3- : (36.77, 38.63, 32.40, and 30.20mg/L)respectively, while the microbiological assay showed no presence of e. coli. CO2 values were 24.00, 21.00,22.67, and 24.33 mg/L for A, B, C and D respectively, Ca2+: (21.33, 22.00, 120.33 and 19.67mg/L), SO42- :(10.67, 8.67, 32.67 and 12.67 mg/L) respectively for A, B, C and D. The pH values showed that rainwaterfrom all the locations were slightly acidic particularly location C. Overall, the water was found fit fordrinking though with a relative high amount of Nitrates in samples A and B and a high CO2 contentespecially in locations D, A and C. These results are indications that the area could experience acid rainunder extreme conditions.